Self-reported Balance Disturbance and Performance-Based Balance Impairment After Concussion in the General Population. Issue 3 (May 2019) - Inness, Elizabeth L.; Sweeny, Michelle; Habib Perez, Olinda; Danells, Cynthia; Chandra, Tharshini; Foster, Evan; Saverino, Cristina; Comper, Paul; Bayley, Mark; Mochizuki, George
Abstract : Objective: To characterize the prevalence of, and relationship between, self-reported balance disturbance and performance-based balance impairment in the general population with concussion. Setting: Rehabilitation hospital outpatient concussion clinic. Participants: One hundred six individuals with concussion (49 males, mean age = 32.4; SD = 11.5 years), mean (SD) = 5 (1.8) days postinjury. Design: Cross-sectional observational study. Main Measures: SCAT3 Symptoms Subscale, Balance Error Scoring System, modified Balance Error Scoring System, and center-of-pressure root-mean-square amplitude and velocity in eyes open and closed conditions. Results: The majority of participants reported balance or dizziness symptoms (54% and 63%, respectively) and demonstrated balance impairment on the Balance Error Scoring System and modified Balance Error Scoring System (66% and 58%, respectively). The prevalence of balance impairment across center-of-pressure measures varied from 32% to 48%. There was no effect of balance or dizziness symptom severity on any of the balance measures ( F 2, 103 = 1.02; P = .44) and ( F 2, 103 = 1.45; P = .10), respectively. There was poor agreement between self-report of balance/dizziness symptoms and identified balance impairment across all balance measures (all κ ⩽ 0.26 and κ ⩽ 0.20, respectively). Conclusions: There was no clear relationship between the subjective experience of balance disturbance and objective measures of balance impairment in the general population. These results have implications for clinical evaluation of postconcussive deficits and determination of recovery. Abstract : Supplemental Digital Content is Available in the Text.